FOOD SECURITY: CONTEMPORARY CHALLENGES AND SOLUTIONS - Yemchuk, Tetiana (Higher School of Security and Economic (Plovdiv, Bulgaria), 2024)
The article examines the key aspects of ensuring food security in the conditions of global changes and economic crises. The main focus is on problems related to uneven access to food, the impact of climate change, political conflicts and socio-economic challenges. The paper analyzes modern technological solutions to increase agricultural productivity, such as genetically modified organisms (GMOs), precision agriculture and vertical farming, which can help overcome food challenges. Particular attention is paid to the social aspects of food security, in particular the support of vulnerable segments of the population, and the role of international cooperation in ensuring a stable food supply.
Keywords: food security; malnutrition; intensification of agricultural production; agriculture; rational use of natural resources